تأثير استخدام وسيلة الكلمات المتقاطعة في تدريس المفردات: دراسة تجريبية في المدرسة لقمان الإيتدائية الإسلامية المتكاملة بادنج - Ritonga, Tipa Nawati; Yufni Faisol; Hanomi (Universitas Islam Ahmad Dahlan Sinjai, 2024)
The aim of this research is to reveal the influence of crossword puzzle media on the Arabic vocabulary skills of students in SDIT Luqman Padang. As for its research approach, it is a quantitative approach using experimental research methods based on field research. Data collection tools are tests, observations, interviews, and documents. The method of data analysis that researchers use is quantitative data analysis with the help of the SPSS 26 program. The results of the study were: 1) The ability of students to learn vocabulary appears from the average pre-test scores in the control class of 71.85 with the category